Decreased Frequency and Improved Outcomes in Invasive Aspergillosis Caused by Aspergillus terreus After the Introduction of Anti-Mold Azole Agents: A 30-Year Study at a Tertiary Cancer Center - Ray Y. Hachem; Hiba Dagher; Anne-Marie Chaftari; Ying Jiang; Andrea Haddad; Saliba Wehbe; Jishna Shrestha; Robin Sherchan; Peter Lamie; Jennifer Makhoul; Patrick Chaftari; Issam I. Raad (Journal of Fungi)
Invasive aspergillosis (IA) is a significant cause of morbidity and mortality in patients with hematological malignancy (HM) and hematopoietic stem cell transplant (HSCT) recipients. Aspergillus terreus is associated with worse outcomes than non-terreus Aspergillus species. Since the introduction of anti-mold azoles in 2002, there have been limited data on the etiology of IA. We retrospectively compared characteristics, antifungal treatments, and outcomes between patients with HM or HSCT infected with A. terreus and those with non-terreus Aspergillus between July 1993 and July 2023. We also examined trends over time in rates of A. terreus and outcomes of this infection. A total of 699 patients with culture-documented IA were analyzed, 537 with non-terreus species and 162 with A. terreus. Types of underlying malignancy, neutropenia, graft-versus-host disease, and anti-mold prophylaxis were similar between the groups. ICU stays and mechanical ventilation were more common among patients with A. terreus (p = 0.002 and 0.003, respectively). The rate of A. terreus decreased significantly from 35.9% during 1993–2003 to 11.2% during 2004–2013 and 16.7% during 2014–2023 (p < 0.0001 each). IA caused by A. terreus showed significant improvements in response to therapy and in overall and IA-associated mortality in the last two decades compared to the first (p < 0.0001). In conclusion, the increased use of anti-mold azoles after 2003 improved outcomes for HM patients with IA caused by A. terreus.